The Pathology of Aljmea fi Tarikh Alarabi Alhadis - farhad Rajabi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
From the very beginning, the study of scholars, poets, and writers’ lives and keeping written records of their literary works and commentaries were considered the first steps towards literary historiography. This movement has developed from the traditional biography writing into modern scientific literary history. Arabic which inherits a modern literature has benefitted from some seminal historiographers who undoubtedly keep a lot of new literary findings in their works.Al-jame fi Tarikhe Al-adabe Al-arabial-hadis is one of the recent loops of Arabic literary historiography circle whose author, Hana Al-fakhuri, has attempted to tender a worthy history by using modern theories. In spite of having some good points, the number of problems and shortcomings has pushed this book away from the scientific criteria of literary history writing and made it close to the traditional works. Because of this important reason, the main objective of this article is to study the pathology of this book from a critical point of view within a descriptive-analytical framework.